Enhanced pool boiling heat transfer on freeze-casted surfaces. (June 2020) - Lin, Tao; Ma, Xiaojing; Quan, Xiaojun; Cheng, P.; Chen, Gang
Highlights: Double-layered biporous coatings are fabricated by freeze casting. Double-layered biporous coatings are applied to enhance pool boiling heat transfer. Biporous coatings are consisting of a biporous layer and a monoporous base layer. Lamellar vertical pores in the biporous layer are formed by templating ice crystals. The heat transfer coefficient on a freeze-casted surface is improved by 180%. Abstract: Distinct from monoporous structures with only one characteristic pore size, biporous structures are characterized by two distinguished pore sizes. In this paper, novel double-layered biporous coatings consisting of a biporous top layer and a monoporous base layer are fabricated by freeze casting from aqueous nickel slurry, where the particle size ( D 50 ) is 400 nm. The biporous layer of the freeze-casted coating is characterized by lamellar vertical large pores formed by templating ice crystals and small pores formed by particle accumulation. The sizes of the large pores are in the order of 10~100 μm depending on coating thicknesses and freezing temperatures, while the sizes of small pores are in the order of ~1 μm. Pool boiling heat transfer performances of freeze-casted double-layered biporous coatings are investigated. For comparison purposes, saturated pool boiling experiments under the same conditions are also carried out on a slurry-evaporation-deposited surface as well as on a smooth surface. Experimental results indicate that freeze-casted coatings enhance boiling heat transfer performance significantly by increasing nucleate site density, decreasing bubble departure diameter, increasing departure frequency, and enhancing surface wickability. Compared to a smooth surface, the inception temperature on a freeze-casted surface is significantly reduced from about 10 K to less than 5 K while the heat transfer coefficient (HTC) and the critical heat flux (CHF) are improved by 180% and 67%, respectively. It is found that there is an optimum coating thickness to maximum HTC due to a tradeoff between nucleation site density and vapor removal efficiency. In addition, liquid slurry frozen at low supercoolings has better boiling heat transfer performance since the pore size is bigger as a result of larger ice crystal size.